Bioactive secondary metabolites from endophytic strains of Neocamarosporium betae collected from desert plants - Liu, Peng; Tan, Yue; Yang, Jian; Wang, Yan-Duo; Li, Qi; Sun, Bing-Da; Xing, Xiao-Ke; Sun, Di-An; Yang, Sheng-Xiang; Ding, Gang (Frontiers in Plant Science, 2023)
Endophytic fungi from desert plants belong to a unique microbial community that has been scarcely investigated chemically and could be a new resource for bioactive natural products. In this study, 13 secondary metabolites (1–13) with diverse carbon skeletons, including a novel polyketide (1) with a unique 5,6-dihydro-4H,7H-2,6-methanopyrano[4,3-d][1,3]dioxocin-7-one ring system and three undescribed polyketides (2, 7, and 11), were obtained from the endophytic fungus Neocamarosporium betae isolated from two desert plant species. Different approaches, including HR-ESI-MS, UV spectroscopy, IR spectroscopy, NMR, and CD, were used to determine the planar and absolute configurations of the compounds. The possible biosynthetic pathways were proposed based on the structural characteristics of compounds 1–13. Compounds 1, 3, 4, and 9 exhibited strong cytotoxicity toward HepG2 cells compared with the positive control. Several metabolites (2, 4–5, 7–9, and 11–13) were phytotoxic to foxtail leaves. The results support the hypothesis that endophytic fungi from special environments, such as desert areas, produce novel bioactive secondary metabolites.